Positive electrode active material for sodium ion battery, preparation method of positive electrode active material, positive electrode plate, battery monomer, battery and electric device

By using sodium-containing metal oxide particles and sodium fluorophosphate coating in the positive electrode material of sodium ion battery, the problem of large volume changes in the positive electrode material during the charge and discharge cycle is solved, and higher structural stability and battery cycle are achieved performance.

CN119447201AActive Publication Date: 2025-02-14CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310948198.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-31
Publication Date
2025-02-14
Estimated Expiration
2043-07-31

AI Technical Summary

Technical Problem

The existing sodium ion battery positive electrode material changes in volume during the charge and discharge cycle, resulting in unstable structure and affecting the cycle stability and life of the battery.

Method used

The positive electrode active material is used with sodium-containing metal oxide particles and a fluorophosphate sodium salt coating layer. The direct contact with the electrolyte solution is reduced through the coating layer of the fluorophosphate sodium salt coating layer, side reactions and dissolution losses are reduced, and structural stability is improved.

Benefits of technology

It effectively limits the volume change of sodium-containing metal oxides in the charge and discharge cycle, and improves the structural stability of the positive electrode material and the cycle stability and life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447201A_ABST
    Figure CN119447201A_ABST
Patent Text Reader

Abstract

The invention provides a positive active material for a sodium ion battery, a preparation method of the positive active material, a positive pole piece, a battery monomer, a battery and an electric device. The positive active material comprises a sodium-containing metal oxide; the coating layer is coated on at least part of the surface of the sodium-containing metal oxide, the coating layer comprises sodium fluorophosphate, and the sodium fluorophosphate comprises one or more of Fe and Ni elements. According to the positive electrode active material, the volume variation of the positive electrode active material in the charge-discharge cycle is improved, and the cycle stability and cycle life of the positive electrode plate containing the positive electrode active material in the battery monomer are improved, so that the battery monomer comprising the positive electrode plate, the battery and the electric device also have corresponding advantages.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of battery devices, and in particular to a positive electrode active material for a sodium ion battery and a preparation method thereof, a positive electrode sheet, a battery cell, a battery and an electrical device. Background Art

[0002] Battery cells represented by sodium-ion batteries rely on the reciprocating intercalation and deintercalation of active ions between the positive and negative electrodes to charge and discharge. They have outstanding characteristics such as high energy density, long cycle life, no pollution, and no memory effect.

[0003] Therefore, battery cells that can be charged and discharged multiple times as clean energy have gradually spread from electronic products to large-scale devices such as electric vehicles to adapt to the sustainable development strategy of the environment and energy. As a result, higher requirements are also placed on the cycle stability of battery cells. Summary of the invention

[0004] The present application provides a positive electrode active material for a sodium ion battery and a preparation method thereof, a positive electrode pole piece, a battery cell, a battery and an electrical device. On the basis of having a high gram capacity, the volume change of the positive electrode active material during the charge and discharge cycle is improved, and the cycle stability and cycle life of the positive electrode pole piece containing the positive electrode active material in the battery cell are improved, so that the battery cell, the battery and the electrical device including the positive electrode pole piece also have corresponding advantages.

[0005] In a first aspect, an embodiment of the present application provides a positive electrode active material, including:

[0006] Sodium-containing metal oxide particles; and

[0007] The coating layer at least partially coats the sodium-containing metal oxide particles, and the coating layer includes sodium fluorophosphate salt, and the sodium fluorophosphate salt includes one or more of Fe and Ni elements.

[0008] According to the technical solution of the embodiment of the present application, on the one hand, the coating layer can reduce the direct contact between the sodium-containing metal oxide and the electrolyte, reduce the occurrence of side reactions related to the sodium-containing metal oxide, reduce the dissolution and loss of the sodium-containing metal oxide, and improve the structural stability of the positive electrode active material, thereby improving the cycle stability of the battery cell containing the positive electrode active material. On the other hand, the volume deformation of the sodium-containing metal oxide during the charge and discharge cycle is large, but the sodium fluorophosphate salt in its surface coating layer has a stable structure, and the volume deformation generated during the active ion extraction / embedding process is very small. Such a coating structure of the sodium-containing metal oxide limits the volume change of the sodium-containing metal oxide during the charge and discharge cycle, and improves the structural stability of the positive electrode material and the cycle stability of the battery.

[0009] When the positive electrode active material comprises sodium-containing metal oxide and sodium fluorophosphate, the positive electrode plate comprising the positive electrode active material has a higher first coulombic efficiency in a battery cell, thereby improving the cycle performance of the battery cell.

[0010] Therefore, the positive electrode active material of the embodiment of the present application is applied to the battery cell. The positive electrode active material has high structural stability and has smaller deformation during the charging and discharging process, thereby enhancing the structural stability of the single cell. At the same time, the positive electrode active material has a higher first coulombic efficiency when applied to the battery, thereby improving the cycle performance of the battery cell and extending the cycle life of the battery cell.

[0011] In some optional embodiments, based on the total mass of the positive electrode active material, the positive electrode active material includes sodium fluorophosphate in a mass percentage content W1 of 0.8%-5%, optionally 2%-4%.

[0012] According to the embodiments of the present application, the mass proportion of sodium fluorophosphate in the positive electrode active material is within the above-mentioned appropriate range, which can make the positive electrode active material have both low impedance and high gram capacity, thereby improving the gram capacity of the sodium-containing metal oxide in the positive electrode active material, thereby improving the cycle stability of the battery and extending the cycle life of the battery.

[0013] In some optional embodiments, the average particle size Dv of the positive electrode active material is 1 The ratio of 50 to the average thickness d of the coating layer in the cross section of the positive electrode active material is 1:(0.02-0.2), and can be optionally 1:(0.024-0.18).

[0014] According to the embodiment of the present application, the average particle size Dv of the positive electrode active material is 1 50 and the average thickness d of the coating layer in the cross section of the positive electrode active material is within the above range, the thickness and content of the coating layer can be further controlled, so that the positive electrode active material has good charge and discharge gram capacity, thereby improving the cycle stability and cycle life of the battery cell of the positive electrode electrode sheet containing the positive electrode active material.

[0015] In some optional embodiments, the average particle size Dv of the positive electrode active material is 1 50 is 5μm-20μm, and can be optionally 5μm-15μm.

[0016] Without intending to be bound by any theory or explanation, when the volume distribution particle size Dv of the positive electrode active material is 1 When the given range is met, the positive electrode active material can have a smaller specific surface area, thereby reducing the hygroscopicity of the positive electrode active material, especially when it comes into contact with air, thereby effectively reducing the water content of the positive electrode active material. This is beneficial to improving the cycle performance of the battery and extending the cycle life of the battery.

[0017] In some optional embodiments, the average thickness d of the coating layer is 0.1-2 μm, optionally 0.2-1.5 μm, and more optionally 0.5-1 μm.

[0018] According to the embodiment of the present application, when the average thickness d of the coating layer is within the above-mentioned suitable range, the positive electrode active material can obtain better stability. Therefore, the positive electrode active material is applied to the battery cell, which can further improve the cycle stability of the battery, reduce the internal resistance and capacity attenuation of the battery, and thus further extend the cycle life of the battery.

[0019] In some optional embodiments, the sodium fluorophosphate salt has the general formula Na x A y (PO4) z F, wherein A includes any one or a combination of Fe and Ni elements; 0<x≤2, 0<y≤2, 0<z≤2; optionally, x+y-3Z=1 or x+2y-3Z=1.

[0020] According to the embodiments of the present application, sodium fluorophosphate is a polyanionic compound that has very little deformation during the battery charge and discharge process, and therefore has good cycle stability. Due to its small proportion in the positive electrode active material, even if its structure is relatively compact, it has no obvious inhibitory effect on the migration rate of sodium ions during the charge and discharge process. The above-mentioned type of sodium fluorophosphate can be used as a zero-strain material to further improve the stability of the positive electrode active material in the charge and discharge electrochemical cycle.

[0021] In some optional embodiments, the sodium-containing metal oxide particles include a structural formula of Na a Ni b Co c Mn f M d O e A metal oxide, wherein 0.5≤a≤1.2, 0≤b≤2, 0≤c≤2, 0≤f≤1, 0≤d≤1.5, 1≤e≤4, A includes one or more of Li and Na; M includes any one of Fe, Al, Zr, Y, La, Zn, Ca, Li, Rb, Cs, W, Ce, Mo, Ba, Ti, Mg, Ta, Nb, V, Sc, Sr, B and Cu elements, or a combination of at least two of them.

[0022] In some optional embodiments, b+c+d+f=1 or b+c+d+f=2.

[0023] In a second aspect, the present application provides a method for preparing the positive electrode active material of the first aspect, comprising:

[0024] mixing an aqueous solution containing a sodium fluorophosphate precursor with an organic suspension containing a sodium-containing metal oxide to obtain a mixed solution;

[0025] The solvent in the mixed solution is removed, and solid-phase sintering is performed in a protective atmosphere to convert the sodium fluorophosphate salt precursor into sodium fluorophosphate salt and form one or more coating layers that at least partially cover the sodium-containing metal oxide particles to obtain a positive electrode active material.

[0026] According to an embodiment of the present application, an aqueous solution containing a sodium fluorophosphate salt precursor is mixed with an organic suspension, which can further improve the uniformity of the coating, so that the sodium-containing metal oxides are each coated with a coating layer, which is beneficial to improving the homogeneity of the positive electrode active material, thereby improving the cycle stability of the positive electrode plate containing the positive electrode active material and reducing the imbalance of the embedding and de-embedding active ions in the positive electrode film layer part of the positive electrode plate.

[0027] In some optional embodiments, the sodium fluorophosphate precursor includes a soluble fluorine-containing salt, a soluble metal salt, and a soluble phosphate, wherein the soluble metal salt includes a salt of any one of Fe and Ni elements or at least two metal elements and a soluble sodium salt.

[0028] In some alternative embodiments, the soluble sodium salt and the soluble phosphate salt are the same substance.

[0029] In some alternative embodiments, the soluble sodium salt and the fluoride-containing salt are the same substance.

[0030] In some optional embodiments, the organic suspension includes an organic solvent, and the organic solvent includes at least one of ethanol and acetone.

[0031] In some optional embodiments, the temperature of solid phase sintering is 500-950 degrees Celsius, optionally 600-800 degrees Celsius.

[0032] In a third aspect, an embodiment of the present application provides a positive electrode plate, comprising a positive electrode current collector and a positive electrode film layer located on at least one side of the positive electrode current collector, wherein the positive electrode film layer comprises the positive electrode active material of the first aspect, or the positive electrode active material prepared by the method of the second aspect.

[0033] According to the embodiments of the present application, the positive electrode plate containing the positive electrode active material can improve its cycle stability in the battery cell and reduce the probability of a sudden change in its cycle capacity.

[0034] In a fourth aspect, an embodiment of the present application provides a battery cell, which includes the positive electrode sheet of the third aspect. The battery cell including the positive electrode sheet also has the corresponding advantages of the positive electrode active material.

[0035] In a fifth aspect, an embodiment of the present application provides a battery, which includes the battery cell of the fourth aspect.

[0036] In a sixth aspect, an embodiment of the present application provides an electrical device, including the battery according to the fifth aspect of the present application, wherein the battery is used to provide electrical energy. The electrical device including the battery also has the corresponding advantages of the positive electrode active material.

[0037] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the embodiments of the present application. Obviously, the drawings described below are only some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without creative work.

[0039] Figure 1 A schematic diagram of the structure of a battery cell provided in some embodiments of the present application is shown;

[0040] Figure 2 An exploded schematic diagram of a battery cell provided in some embodiments of the present application is shown;

[0041] Figure 3 A schematic diagram of the structure of a battery module provided in some embodiments of the present application is shown;

[0042] Figure 4 A schematic diagram of the structure of a battery pack provided in some embodiments of the present application is shown;

[0043] Figure 5 Shows Figure 4 An exploded schematic diagram of a battery pack is shown;

[0044] Figure 6 A schematic diagram of an electrical device provided in some embodiments of the present application is shown.

[0045] The reference numerals are as follows: 1. battery pack; 2. upper case; 3. lower case; 4. battery module; 5. battery cell; 51. shell; 52. electrode assembly; 53. cover plate.

[0046] In the drawings, the drawings are not necessarily drawn to scale. DETAILED DESCRIPTION

[0047] Hereinafter, the phosphate composite positive electrode active material and its preparation method, positive electrode sheet, battery cell, battery and electric device of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0048] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0049] If not otherwise specified, all embodiments and optional embodiments of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.

[0050] Unless otherwise specified, all technical features and optional technical features of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.

[0051] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0052] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or included, or may only include or include the listed components.

[0053] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0054] In this article, the term "coating" refers to a material layer coated on the kernel, and the material layer can completely or partially coat the kernel. The term "coating" is used just for ease of description and is not intended to limit the present invention. In addition, each coating can be completely coated or partially coated.

[0055] If not otherwise specified, in this application, the terms "first", "second", "third", etc. are used to distinguish different objects rather than to describe a specific order or a primary-secondary relationship.

[0056] In the present application, the terms "plurality" and "multiple" refer to two or more.

[0057] In this application, the battery will be accompanied by Na deintercalation and consumption during the charge and discharge process, and the molar content of Na is different when the battery is discharged to different states. In the list of positive electrode materials in this application, the molar content of Na is the initial state of the material, that is, the state before feeding. The positive electrode material is used in the battery system, and the molar content of Na will change after charge and discharge cycles.

[0058] In the list of positive electrode materials in this application, the molar content of O is only a theoretical value. The release of oxygen from the lattice will cause the molar content of oxygen to change, and the actual molar content of O will fluctuate.

[0059] In the present application, the battery cell may include a sodium ion battery, etc., which is not limited in the present embodiment. The battery cell may be an aqueous battery or an oil battery, which is not limited in the present embodiment. The battery cell may be a flat body, a rectangular parallelepiped or other shapes, etc., which is not limited in the present embodiment.

[0060] Unless otherwise specified, the terms used in this application have the commonly understood meanings that are commonly understood by those skilled in the art.

[0061] Unless otherwise specified, the values ​​of the parameters mentioned in this application can be measured by various test methods commonly used in the art, for example, they can be measured according to the test methods given in the examples of this application. Unless otherwise specified, the test temperature of each parameter is 25°C.

[0062] Sodium fluorophosphate is used as a positive electrode material in battery cells. Thanks to the inductive effect of fluorine, it has a high operating voltage (2.0V-4.0V), a low theoretical specific capacity (100mah g-1) and a small volume change (<4%). The nearly zero-strain material has become a positive electrode material for sodium-ion batteries with broad application prospects. The promotion and application of sodium fluorophosphate mainly faces two challenges: first, the material itself has poor conductivity, resulting in poor rate performance; second, the actual capacity is limited due to the low sodium storage utilization rate of the active material (especially the bulk material). Due to the low electronic conductivity and poor cycle performance of sodium fluorophosphate, the electrochemical performance is greatly affected. In addition, the differences in raw material mixing, synthesis process and method during the synthesis process lead to the easy generation of impurities in the material synthesis, and affect its discharge specific capacity and cycle stability. Therefore, the promotion and application of this material is limited.

[0063] Layered oxides have the advantages of high theoretical specific capacity and high compaction density, and their gram capacity is 100-200 mAh g -1 , such as NaCoO2. Layered oxides are one of the most promising cathode materials for sodium-ion batteries that can be commercialized. At the same time, they also have disadvantages such as slightly poor cycle performance and poor stability in air. Modification of layered oxides is the main means to improve the cycle performance of electrode materials.

[0064] In view of this, the inventors have improved the phosphate composite positive electrode active material. In view of this, the present application provides a positive electrode active material that can improve the cycle stability and cycle life of a battery cell containing the positive electrode active material while taking into account its high gram capacity.

[0065] Positive electrode active material

[0066] In a first aspect, an embodiment of the present application provides a positive electrode active material, including:

[0067] Sodium-containing metal oxide particles; and

[0068] The coating layer at least partially coats the sodium-containing metal oxide particles, and the coating layer includes sodium fluorophosphate salt, and the sodium fluorophosphate salt includes one or more of Fe and Ni elements.

[0069] According to the technical solution of the embodiment of the present application, on the one hand, the coating layer can reduce the direct contact between the sodium-containing metal oxide and the electrolyte, reduce the occurrence of side reactions related to the sodium-containing metal oxide, reduce the dissolution and loss of the sodium-containing metal oxide, and improve the structural stability of the positive electrode active material, thereby improving the cycle stability of the battery cell containing the positive electrode active material. On the other hand, the volume deformation of the sodium-containing metal oxide during the charge and discharge cycle is large, but the sodium fluorophosphate salt in its surface coating layer has a stable structure, and the volume deformation generated during the active ion extraction / embedding process is very small. Such a coating structure of the sodium-containing metal oxide limits the volume change of the sodium-containing metal oxide during the charge and discharge cycle, and improves the structural stability of the positive electrode material and the cycle stability of the battery.

[0070] When the positive electrode active material comprises sodium-containing metal oxide and sodium fluorophosphate, the positive electrode plate comprising the positive electrode active material has a higher first coulombic efficiency in a battery cell, thereby improving the cycle stability of the battery cell.

[0071] Analysis shows that the reason why the first coulombic efficiency of the positive electrode active material of the present application is improved compared with that of simple layered metal oxides may be that the sodium fluorophosphate containing Fe and Ni elements has higher conductivity than sodium-containing metal oxide particles. Even though the degree of deintercalation of active sodium ions by sodium fluorophosphate is slightly weaker than that of layered metal oxides, it contains Fe and Ni elements, and their interaction with fluorine element enhances the ability of sodium fluorophosphate to deintercalate sodium ions. Therefore, its ability to conduct electrons and the efficiency of deintercalation of active sodium ions are enhanced, thereby improving its first coulombic efficiency.

[0072] Sodium fluorophosphate contains Fe and Ni elements, which are present in the coating layer of sodium fluorophosphate. On the one hand, Fe and Ni are relatively common metals, so sodium iron fluorophosphate is relatively low-cost as a positive electrode material; sodium atoms, iron atoms and nickel atoms in sodium fluorophosphate can provide a higher theoretical capacity in the electrochemical cycle of battery cells, which is beneficial to increase the energy density of the battery; and sodium fluorophosphate containing Fe and Ni elements has a good cycle life and can provide a long-lasting battery life.

[0073] The Fe element exists in sodium fluorophosphate, which can improve the magnetic properties of sodium fluorophosphate. When sodium fluorophosphate is in the positive electrode active material, it is contained in the positive electrode plate in the battery cell, which can offset a part of the electric field force of the battery cell, thereby facilitating the deintercalation of active sodium ions and improving the first coulomb efficiency. And the Fe element exists in sodium fluorophosphate, which can improve the stability and corrosion resistance of sodium fluorophosphate.

[0074] The Ni element exists in sodium fluorophosphate, which can improve the sodium ion insertion / extraction capacity of sodium fluorophosphate. During the charge and discharge process of the battery cell, each nickel element can embed or release multiple active sodium ions, thereby storing more charge and improving the initial coulombic efficiency. The Ni element exhibits good electrochemical stability in sodium ion batteries, which reduces the serious structural damage or accumulation of electrochemical reaction byproducts in the positive electrode active material during multiple charge and discharge cycles, and is conducive to long-term stability.

[0075] Therefore, the positive electrode active material of the embodiment of the present application is applied to the battery cell. The positive electrode active material has high structural stability and has smaller deformation during the charging and discharging process, thereby enhancing the structural stability of the single cell. At the same time, the positive electrode active material has a higher first coulombic efficiency when applied to the battery, thereby improving the cycle performance of the battery cell and extending the cycle life of the battery cell.

[0076] In some embodiments, the positive electrode active material is a core-shell structure, wherein the core material comprises a sodium-containing metal oxide; and the shell comprises sodium fluorophosphate.

[0077] Without intending to be limited by any theory or explanation, in the positive electrode active material of the embodiment of the present application, the sodium-containing metal oxide has relatively poor stability in the air. The coating layer is arranged on the surface of the sodium-containing metal oxide, which can reduce the contact between the sodium-containing metal oxide and the air. In the battery cell, it can reduce the contact between the sodium-containing metal oxide and the electrolyte, thereby improving the stability performance of the positive electrode active material.

[0078] In some optional embodiments, based on the total mass of the positive electrode active material, the positive electrode active material includes sodium fluorophosphate in a mass percentage content W1 of 0.8%-5%, optionally 2%-4%.

[0079] Optionally, the positive electrode active material includes sodium fluorophosphate whose mass percentage W1 can be any value among 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5.0%, or a range composed of any two of the above values.

[0080] According to the embodiment of the present application, the mass proportion of sodium fluorophosphate in the positive electrode active material is within the above-mentioned suitable range, so that the positive electrode active material can have a thinner coating layer, and the mass proportion of sodium fluorophosphate in the positive electrode active material is small, and there is no obvious inhibitory effect on the migration rate of sodium ions during the charge and discharge process. Thus, the first coulomb efficiency of the positive electrode active material can be improved.

[0081] The mass percentage of sodium fluorophosphate in the positive electrode active material has a meaning known in the art and can be determined by equipment and methods known in the art. As an example, a certain mass of positive electrode material is dissolved in aqua regia, diluted a certain multiple and tested by inductively coupled plasma atomic emission spectrometry (ICP-AES) to obtain the content of a certain metal element in the coating, and the mass of sodium fluorophosphate is calculated based on the content of a certain metal element. In some embodiments, the ratio of the mass of sodium fluorophosphate to the mass of the positive electrode active material can be the mass percentage of the coating layer.

[0082] According to the embodiments of the present application, the mass proportion of sodium fluorophosphate in the positive electrode active material is within the above-mentioned appropriate range, thereby improving the gram capacity of the positive electrode active material, thereby improving the cycle stability of the battery and extending the cycle life of the battery.

[0083] In some optional embodiments, the average particle size Dv of the positive electrode active material is 1 The ratio of 50 to the average thickness d of the coating layer in the cross section of the positive electrode active material is 1:(0.02-0.2), and can be optionally 1:(0.024-0.18).

[0084] Optionally, the average particle size Dv of the positive electrode active material 150 and the average thickness d of the coating layer in the cross section of the positive electrode active material may be 1:0.021, 1:0.026, 1:0.031, 1:0.036, 1:0.041, 1:0.046, 1:0.051, 1:0.056, 1:0.061, 1:0.066, 1:0.071, 1:0.076, 1:0.081, 1:0.086, 1:0.091, 1:0.096, 1:0.101, 1:0. Any value among 1:0.106,1:0.111,1:0.116,1:0.121,1:0.126,1:0.131,1:0.136,1:0.141,1:0.146,1:0.151,1:0.156,1:0.161,1:0.166,1:0.171,1:0.176,1:0.181,1:0.186,1:0.191,1:0.196,1:0.2, or a range consisting of any two of the above values.

[0085] According to the embodiment of the present application, the average particle size Dv of the positive electrode active material is 1 50 and the average thickness d of the coating layer in the cross section of the positive electrode active material is within the above range, the thickness and content of the coating layer can be further controlled, so that the positive electrode active material has both good specific surface area and large gram capacity, thereby improving the cycle stability and cycle life of the battery cell containing the positive electrode plate.

[0086] In some optional embodiments, the average particle size Dv of the positive electrode active material is 1 50 is 5μm-20μm, and can be optionally 5μm-15μm.

[0087] Optionally, the average particle size Dv of the positive electrode active material 1 50 can be any value among 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, 20μm, or a range consisting of any two of the above values.

[0088] Without intending to be bound by any theory or explanation, when the volume distribution particle size Dv of the positive electrode active material is 1 When 50 satisfies the given range, the positive electrode active material can have a suitable specific surface area, which is beneficial to improving the cycle performance of the battery and extending the cycle life of the battery.

[0089] In addition, the average particle size Dv of the positive electrode active material 1When the given range is met, the hygroscopicity of the positive electrode active material can be reduced, especially when it comes into contact with air, thereby effectively reducing the water content of the positive electrode active material. Thus, the performance of the positive electrode sheet containing the positive electrode active material in the battery cell is improved.

[0090] Volume distribution particle size Dv of positive electrode active material 1 50 has a well-known meaning in the art, which can represent the particle size corresponding to the cumulative particle size distribution percentage of the positive electrode active material in the volume-based particle size distribution of 50%. The volume distribution particle size Dv50 can be measured using equipment and methods known in the art. For example, it can be measured with a laser particle size analyzer (e.g., Malvern Master Size 3000) with reference to GB / T 19077-2016 particle size distribution laser diffraction method.

[0091] In some optional embodiments, the average thickness d of the coating layer is 0.1-2 μm, optionally 0.2-1.5 μm, and more optionally 0.5-1 μm.

[0092] Optionally, the average thickness d of the coating layer can be any value among 0.1μm, 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1.0μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, 1.6μm, 1.7μm, 1.8μm, 1.9μm, 2.0μm, or a range consisting of any two of the above values.

[0093] According to the embodiment of the present application, when the average thickness d of the coating layer is within the above-mentioned suitable range, the positive electrode active material can have a larger specific surface area and better stability. Therefore, the positive electrode active material is applied to the battery cell, which can further improve the cycle stability of the battery, reduce the internal resistance and capacity attenuation of the battery, and thus further extend the cycle life of the battery.

[0094] The average thickness of the above-mentioned coating layer may have a meaning known in the art and may be determined by equipment and methods known in the art. As an example, it can be tested by the following method: the positive electrode active material and the binder are mixed evenly, coated on the surface of the positive electrode current collector, and prepared into a positive electrode sheet through drying, cold pressing and other steps (when sampling from the battery, the battery can be directly disassembled, the positive electrode sheet can be taken out and dried); randomly select an area, perform argon ion cross-section polishing, and take an electron microscope image (SEM image) with a magnification of more than 3000 times (for example, it can be 3000 times or 5000 times); process the SEM image and adjust the appropriate contrast until the outline of the positive electrode active material can be clearly seen; use software to count the particle size of each positive electrode active material in the cross section, as well as the thickness of the single-layer coating layer, to obtain the volume distribution particle size Dv of the sodium-containing metal oxide. 1 50. Thickness of coating layer. As another example, the positive electrode active material powder can be directly subjected to argon ion cross-section polishing, and a SEM image can be taken to determine the average thickness of the coating layer through the SEM image.

[0095] In some optional embodiments, the sodium fluorophosphate salt has the general formula Na x A y (PO4) z F, wherein A includes any one or a combination of Fe and Ni elements; 0<x≤2, 0<y≤2, 0<z≤2. In some optional embodiments, x+y-3Z=1 or x+2y-3Z=1.

[0096] In some optional embodiments, A includes any one or a combination of Fe and Ni elements.

[0097] According to the embodiments of the present application, sodium fluorophosphate is a polyanionic compound that has very little deformation during the battery charge and discharge process, and therefore has good cycle stability. The above-mentioned sodium fluorophosphate is a zero-strain material, which further improves the stability of the positive electrode active material in the charge and discharge electrochemical cycle in the positive electrode active material.

[0098] According to the embodiment of the present application, during the charge and discharge cycle of the battery, the volume change of the sodium fluorophosphate salt in the positive electrode active material containing the above sodium fluorophosphate salt is small when the sodium fluorophosphate salt is extracted and embedded in the active sodium ions, thereby reducing the volume change of the positive electrode active material during the charge and discharge cycle. As a result, the stability of the positive electrode active material can be improved, thereby improving the cycle stability of the battery and extending the cycle life of the battery.

[0099] In some optional embodiments, the sodium-containing metal oxide particles include a structural formula of Na a Ni b Co c Mn fM d O e The metal oxide of, where 0.5 ≤ a ≤ 1.2, 0 ≤ b ≤ 2, 0 ≤ c ≤ 2, 0 ≤ f ≤ 1, 0 ≤ d ≤ 1.5, 1 ≤ e ≤ 4, A includes one or more of Li and Na; M includes any one or a combination of at least two of the elements Fe, Al, Zr, Y, La, Zn, Ca, Li, Rb, Cs, W, Ce, Mo, Ba, Ti, Mg, Ta, Nb, V, Sc, Sr, B, and Cu; optionally, b + c + d + f = 1 or b + c + d + f = 2.

[0100] In some alternative embodiments, the sodium-containing metal oxide has the general formula Na a MO2, where 0.2 < a ≤ 2; M is any one or a combination of several of the elements Mn, Fe, Ni, Co, Al, Zr, Y, La, Zn, Ca, Li, Rb, Cs, W, Ce, Mo, Ba, Ti, Mg, Ta, Nb, V, Sc, Sr, B, and Cu.

[0101] According to an embodiment of the present application, Fe can be divalent positive in the sodium-containing metal oxide.

[0102] According to an embodiment of the present application, during the charge and discharge cycle of the battery with the positive electrode active material containing the above general formula, a certain amount of active sodium released from the sodium-containing metal oxide has a reduced volume change under the coating of the coating layer, which can improve the stability of the sodium-containing metal oxide, thereby improving the cycle stability of the battery and extending the cycle life of the battery.

[0103] As an example of the above sodium-containing metal oxide, for example, the following can be listed:

[0104] Na 1-x Cu h Fe k Mn l M 1 m O 2-y , where M 1 is one or several of Li, Be, B, Mg, Al, K, Ca, Ti, Co, Ni, Zn, Ga, Sr, Y, Nb, Mo, In, Sn, and Ba, 0 < x ≤ 0.5, 0 < h ≤ 0.24, 0 ≤ k ≤ 0.32, 0 < l ≤ 0.68, 0 ≤ m < 0.1, h + k + l + m = 1, 0 ≤ y < 0.2;

[0105] Na 0.67 Mn 0.7 Ni z M 2 0.3-z O2, where M 2is one or more of Li, Mg, Al, Ca, Ti, Fe, Cu, Zn and Ba, 0 <z≤0.1;

[0106] Na a Li b Ni c Mn d Fe e O2, where 0.5≤a≤1, 0 <b<0.2,0<c<0.3,0.67<d+e<0.8,b+c+d+e=1。

[0107] As an example, the positive electrode active material may include NaCoO2, NaNiO2, NaMnO2, NaMn2O4, NaNi 1 / 3 Co 1 / 3 Mn 1 / 3O2、NaNi 0.5 Co 0.2 Mn 0.3 O2、LiNi 0.6 Co 0.2 Mn 0.2 O2、NaNi 0.8 Co 0.1 Mn 0.1 O2、NaNi 0.85 Co 0.15 Al 0.05 O2、NaMn 0.33 Ni 0.27 Fe 0.33 Zn 0.06 O2、NaMn 0.33 Ni 0.27 Fe 0.33 Zn 0.06 O2、Na 0.8 Ni 0.365 Fe 0.07 Mn 0.545 La 0.02 One or more of O2, NaFePO4 and NaMnPO4.

[0108] Method for preparing positive electrode active material

[0109] In a second aspect, the present application provides a method for preparing the positive electrode active material of the first aspect, comprising:

[0110] Step a, providing an organic suspension containing a sodium-containing metal oxide;

[0111] Step b, mixing an aqueous solution containing a sodium fluorophosphate precursor with an organic suspension to obtain a mixed solution;

[0112] Step c, removing the solvent from the mixed solution, and performing solid phase sintering in a protective atmosphere to form a coating layer on the surface of the sodium-containing metal oxide to obtain a positive electrode active material, wherein the coating layer includes sodium fluorophosphate.

[0113] In step a, the sodium-containing metal oxide may be as described in any embodiment of the first aspect, and the embodiments of the sodium-containing metal oxide have been described and illustrated in detail above, which will not be repeated here. The sodium-containing metal oxide may be commercially available or prepared by methods known in the art.

[0114] In step b, the coating layer may be as described in any embodiment of the first aspect. The examples of the components of the coating layer have been described and illustrated in detail above and will not be repeated here.

[0115] In some optional embodiments, the sodium fluorophosphate precursor includes a soluble fluorine-containing salt, a soluble metal salt, a soluble phosphate and a soluble sodium salt, wherein the soluble metal salt includes a combination of salts of any one of Fe and Ni elements or at least two metal elements and a soluble sodium salt.

[0116] In some embodiments, the soluble phosphate includes monohydrogen phosphate and dihydrogen phosphate, such as ammonium hydrogen phosphate (NH4H2PO4), sodium hydrogen phosphate (NaH2PO4), potassium hydrogen phosphate (KH2PO4), and the like.

[0117] Monohydrogen phosphate, i.e. monohydrogen phosphate, may be sodium dihydrogen phosphate (Na2HPO4), potassium dihydrogen phosphate (K2HPO4), or the like.

[0118] Dihydrogen phosphate is dihydrogen phosphate, which can be sodium dihydrogen phosphate (NaH2PO4), potassium dihydrogen phosphate (KH2PO4), etc. Fluoride-containing salts can be sodium fluoride, ammonium fluoride, potassium fluoride, etc.

[0119] In some embodiments, the soluble sodium salt may be a sodium-containing compound known in the art that can be used to prepare a phosphate positive electrode active material, for example, the soluble sodium salt may include one or more of sodium hydroxide, sodium carbonate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium nitrate and sodium acetate. In the preparation method of the positive electrode active material provided in the present application, the addition amount of each raw material may conform to the stoichiometric ratio of the target phosphate composite positive electrode active material.

[0120] In some embodiments, the amount of the sodium source added may be slightly excessive, for example, 100%-110% of the theoretical mass of the sodium source, where the theoretical mass of the sodium source is calculated based on the stoichiometric ratio of the positive electrode active material.

[0121] In some optional embodiments, the soluble metal salt and the soluble phosphate are the same substance. The soluble metal salt includes one or more of nickel chloride, nickel nitrate, nickel sulfate, nickel nitrate, nickel acetate, ferrous chloride, ferric chloride, ferrous nitrate, ferric nitrate, ferrous sulfate, ferric sulfate, and ferric acetate.

[0122] In some optional embodiments, the soluble sodium salt and the soluble phosphate are the same substance, which can be sodium hydrogen phosphate (NaH2PO4) or sodium dihydrogen phosphate (Na2HPO4).

[0123] In some optional embodiments, the soluble sodium salt and the fluoride-containing salt are the same substance, which may be sodium fluoride.

[0124] In some optional embodiments, the organic suspension includes an organic solvent, and the organic solvent includes at least one of ethanol and acetone.

[0125] In some optional embodiments, the average particle size Dv of the sodium-containing metal oxide is 2 50 is 4.8μm-16μm, optional is 6μm-12μm.

[0126] Optionally, the average particle size Dv of the sodium-containing metal oxide is 2 50 can be any value among 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, or a range consisting of any two of the above values.

[0127] Without intending to be bound by any theory or explanation, when the average particle size Dv of the sodium-containing metal oxide is 2 When the given range is met, the hygroscopicity of the sodium-containing metal oxide can be reduced, and the metal oxide can be better coated by the coating layer, thereby improving the cycle stability of the battery.

[0128] In some optional embodiments, the temperature of solid phase sintering is 500-950 degrees Celsius, and optionally 600-800 degrees Celsius. In step c, the temperature and time of solid phase sintering can be the temperature and time known in the art, and those skilled in the art can adjust them as needed.

[0129] Positive electrode

[0130] In a third aspect, an embodiment of the present application provides a positive electrode plate, comprising a positive electrode current collector and a positive electrode film layer located on at least one side of the positive electrode current collector, wherein the positive electrode film layer comprises the positive electrode active material of the first aspect, or the positive electrode active material prepared by the method of the second aspect.

[0131] The positive electrode plate of the embodiment of the present application includes the positive electrode active material of the first aspect, or the positive electrode active material prepared according to the method of the second aspect, and is applied to a battery cell, which can improve the cycle stability of the battery cell and extend the cycle life of the battery cell.

[0132] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0133] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0134] In some embodiments, the positive electrode film layer may further include a second positive electrode active material, and the second positive electrode active material may be a positive electrode active material for sodium ion batteries known in the art. As an example, the second positive electrode material may also include one or more of a sodium-containing transition metal oxide, a polyanionic compound, and a Prussian blue compound. The sodium ion battery of the embodiment of the present application may use a negative electrode sheet using hard carbon as the negative electrode active material, and a positive electrode sheet including one or more positive electrode active materials of sodium transition metal oxides, polyanionic compounds, and Prussian blue compounds, so that the sodium ion battery has higher capacity performance and energy density.

[0135] Examples of the polyanionic compound include:

[0136] A 1 f M 3 g (PO4) i O j X 1 3-j , wherein A is one or more of H, Li, Na, K and NH4, M 3 is one or more of Ti, Cr, Mn, Fe, Co, Ni, V, Cu and Zn, X 1 is one or more of F, Cl and Br, 0 <f≤4,0<g≤2,1≤i≤3,0≤j≤2;

[0137] Na n M4 PO4X 2 , wherein M 4 is one or more of Mn, Fe, Co, Ni, Cu, and Zn, and X 2 is one or more of F, Cl, and Br; 0 < n ≤ 2;

[0138] Na p M 5 q (SO4)3, wherein M 5 is one or more of Mn, Fe, Co, Ni, Cu, and Zn; 0 < p ≤ 2, 0 < q ≤ 2;

[0139] Na s Mn t Fe 3-t (PO4)2(P2O7), wherein 0 < s ≤ 4, 0 ≤ t ≤ 3, for example, t is 0, 1, 1.5, 2, or 3.

[0140] As an example of the above Prussian blue - like compounds, for example, the following can be listed:

[0141] A u M 6 v [M 7 (CN)6] w ·xH2O, wherein A is one or more of H + , NH4 + , alkali metal cations, and alkaline earth metal cations, M 6 and M 7 are each independently one or more of transition metal cations; 0 < u ≤ 2, 0 < v ≤ 1, 0 < w ≤ 1, 0 < x < 6. For example, A is H + , Li + , Na + , K + , NH4 + , Rb + , Cs + , Fr + , Be 2+ , Mg 2+ , Ca 2+ , Sr 2+ , Ba 2+ and Ra 2+ ; M 6 and M 7 are each independently cations of one or more transition metal elements of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Sn, and W. Optionally, A is Li + , Na + , and K+ One or more of M 6 Mn is a cation of one or more transition metal elements among Mn, Fe, Co, Ni and Cu. 7 It is a cation of one or more transition metal elements among Mn, Fe, Co, Ni and Cu.

[0142] In some implementations, the weight percentage of the conductive agent in the positive electrode material layer is greater than or equal to 0.5 wt %, which is beneficial for constructing a better electronic conductive network.

[0143] In some implementations, the weight percentage of the binder in the positive electrode material layer is greater than or equal to 0.5 wt %, which is beneficial for obtaining good bonding performance.

[0144] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0145] In some embodiments, the positive electrode film layer may further include a conductive agent and an optional dispersant. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0146] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0147] Battery Cell

[0148] In a fourth aspect, an embodiment of the present application provides a battery cell comprising the positive electrode plate of the third aspect.

[0149] The battery cell includes the above-mentioned positive electrode sheet and negative electrode sheet. The structure and composition of the negative electrode sheet can be selected according to the type of the battery cell, and the embodiment of the present application is not limited to this.

[0150] In some embodiments, the negative electrode sheet may include a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector and including a negative electrode active material. For example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0151] The negative electrode active material may adopt materials known in the art. As an example, the negative electrode active material may include, but is not limited to, one or more of natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and sodium titanate. Silicon-based materials may include one or more of elemental silicon, silicon oxide, silicon-carbon composite, silicon-nitrogen composite, and silicon alloy materials. Tin-based materials may include one or more of elemental tin, tin oxide, and tin alloy materials. The present application is not limited to these materials, and other conventionally known materials that can be used as negative electrode active materials may also be used.

[0152] In some embodiments, the negative electrode film layer may further include a negative electrode conductive agent. The present application has no particular restrictions on the type of the negative electrode conductive agent. As an example, the negative electrode conductive agent may include one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0153] In some embodiments, the negative electrode film layer may further include a negative electrode binder. The present application has no particular restrictions on the type of negative electrode binder. As an example, the negative electrode binder may include styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA) and carboxymethyl chitosan (CMCS). One or more.

[0154] In some embodiments, the negative electrode film layer may further include other additives. As an example, the other additives may include a thickener, such as sodium carboxymethyl cellulose (CMC), a PTC thermistor material, and the like.

[0155] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include one or more of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base layer may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).

[0156] The negative electrode film layer is usually formed by coating the negative electrode slurry on the negative electrode current collector, drying and cold pressing. The negative electrode slurry is usually formed by dispersing the negative electrode active material, optional negative electrode conductive agent, optional negative electrode binder, other optional auxiliary agents, etc. in a solvent and stirring them uniformly. The solvent can be N-methylpyrrolidone (NMP) or deionized water, but is not limited thereto.

[0157] The negative electrode plate does not exclude other additional functional layers besides the negative electrode film layer. For example, in some embodiments, the negative electrode plate may also include a conductive primer layer (e.g., composed of a conductive agent and a binder) sandwiched between the negative electrode current collector and the negative electrode film layer and disposed on the surface of the negative electrode current collector; in some embodiments, the negative electrode plate may also include a protective layer covering the surface of the negative electrode film layer.

[0158] In some embodiments, the negative electrode plate may include a negative electrode current collector and a metal layer disposed on at least one surface of the negative electrode current collector, and the metal layer may include one or more of a single substance of sodium and a sodium alloy.

[0159] The sodium alloy may be an alloy formed by metallic sodium and other metallic elements or non-metallic elements. As an example, the other metallic elements in the sodium alloy may include one or more of tin, zinc, aluminum, magnesium, silver, gold, gallium, indium, and platinum, and the non-metallic elements in the sodium alloy may include one or more of boron, carbon, and silicon.

[0160] In some embodiments, the negative electrode plate may further include a negative electrode current collector but not a metal layer, thereby forming a negative electrode metal-free battery cell.

[0161] In some embodiments, the negative electrode plate may also be directly made of a sheet (or foil) of sodium or a sodium alloy.

[0162] [Electrolytes]

[0163] The electrolyte plays a role in conducting active ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can include one or more of a solid electrolyte and a liquid electrolyte (i.e., an electrolyte).

[0164] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0165] In some embodiments, the electrolyte may include an organic solvent and a sodium salt, and any organic solvent and sodium salt that can be used in sodium ion batteries can be selected according to actual needs. As an example, the organic solvent may be one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC); the sodium salt may be one or more of NaPF6, NaClO4, NaBCl4, NaSO3CF3 and Na(CH3)C6H4SO3.

[0166] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0167] In some embodiments, the electrolyte may also optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature or low temperature performance, etc. In some embodiments, the electrolyte may also optionally include additives. For example, the additives may include negative electrode film-forming additives, may also include positive electrode film-forming additives, and may also include additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, additives that improve battery low temperature power performance, etc.

[0168] [Isolation film]

[0169] Battery cells using electrolytes and some battery cells using solid electrolytes also include a separator. The separator is arranged between the positive electrode and the negative electrode, and mainly plays the role of preventing the positive and negative electrodes from short-circuiting, while allowing active ions to pass through. The present application has no particular restrictions on the type of separator, and any known porous structure separator with good chemical stability and mechanical stability can be selected.

[0170] In some embodiments, the material of the isolation membrane may include one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film. When the isolation membrane is a multi-layer composite film, the materials of each layer are the same or different.

[0171] The preparation method of battery cells is well known. In some embodiments, the positive electrode sheet, the separator, the negative electrode sheet and the electrolyte can be assembled to form a battery cell. As an example, the positive electrode sheet, the separator, and the negative electrode sheet can be formed into an electrode assembly through a winding process and / or a lamination process, and the electrode assembly is placed in an outer package, and the above-mentioned electrolyte is injected after drying. After vacuum packaging, standing, formation, shaping and other processes, a battery cell is obtained. Multiple battery cells can also be further connected in series, in parallel or in mixed connection to form a battery module. Multiple battery modules can also be connected in series, in parallel or in mixed connection to form a battery pack. In some embodiments, multiple battery cells can also directly form a battery pack.

[0172] Battery

[0173] In a fifth aspect, an embodiment of the present application provides a battery, comprising the battery cell of the fourth aspect.

[0174] The battery mentioned in the embodiments of the present application may be a single physical module including one or more battery cells to provide higher voltage and capacity. For example, the battery mentioned in the present application may include a battery cell, a battery module or a battery pack.

[0175] A battery cell is the smallest unit of a battery, which can independently realize the functions of charging and discharging. The battery cell can be cylindrical, rectangular or in other shapes, etc., which is not limited in the embodiments of the present application. Figure 1 The battery cell 5 is a rectangular parallelepiped structure as an example.

[0176] When there are multiple battery cells, the multiple battery cells are connected in series, in parallel, or in mixed connection through a busbar. In some embodiments, the battery may be a battery module; when there are multiple battery cells, the multiple battery cells are arranged and fixed to form a battery module. In some embodiments, the battery may be a battery pack, and the battery includes a case and battery cells, and the battery cells or battery modules are accommodated in the case. In some embodiments, the case may serve as part of the chassis structure of the vehicle. For example, part of the case may become at least a part of the floor of the vehicle, or part of the case may become at least a part of the crossbeam and longitudinal beam of the vehicle.

[0177] In some embodiments, the battery may be an energy storage device, which includes an energy storage container, an energy storage cabinet, and the like.

[0178] The battery cells mentioned in the embodiments of the present application include sodium ion primary battery cells, sodium ion battery cells, sodium metal battery cells, negative electrode-free sodium metal battery cells, etc., which are not limited in the embodiments of the present application.

[0179] The battery cell includes an electrode assembly. The electrode assembly may be a winding structure or a laminated structure, which is not limited in the present application.

[0180] The battery cell also includes an outer package, which can be used to encapsulate the electrode assembly and the electrolyte. The outer package can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT) and polybutylene succinate (PBS).

[0181] In some embodiments, Figure 2As shown, the outer package may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The electrode assembly 52 is encapsulated in the receiving cavity. The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, which can be adjusted according to demand.

[0182] In some embodiments, battery cells may be assembled into a battery module. The battery module may contain multiple battery cells, and the specific number may be adjusted according to the application and capacity of the battery module. Figure 3 FIG. 4 is a schematic diagram of a battery module 4 as an example. Figure 3 As shown, in the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.

[0183] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.

[0184] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.

[0185] Figure 4 and Figure 5 FIG. 1 is a schematic diagram of a battery pack 1 as an example. Figure 4 and Figure 5 As shown, the battery pack 1 may include a box body and a plurality of battery modules 4 disposed in the box body. The box body includes an upper box body 2 and a lower box body 3, and the upper box body 2 is used to cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the box body in any manner.

[0186] Electrical devices

[0187] In a sixth aspect, an embodiment of the present application provides an electrical device, including the battery of the fifth aspect, and the battery is used to provide electrical energy. The battery can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device can be, but is not limited to, a mobile device (such as a mobile phone, a tablet computer, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.

[0188] The electrical device can select a specific type of battery, such as a battery cell, a battery module or a battery pack, according to its usage requirements.

[0189] Figure 6 Schematic diagram of an electric device as an example. The electric device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the requirements of the electric device for high power and high energy density, a battery pack or a battery module can be used as a power source.

[0190] As another example, the electric device may be a mobile phone, a tablet computer, a notebook computer, etc. The electric device is usually required to be light and thin, and a battery cell may be used as a power source.

[0191] Example

[0192] The following examples describe the disclosure of the present application in more detail, and these examples are intended for illustrative purposes only, as various modifications and variations within the scope of the disclosure of the present application will be apparent to those skilled in the art. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.

[0193] Example 1-1

[0194] According to the chemical formula of layered oxide positive electrode material NaNi 0.5 Mn 0.5 The molar ratio of different elements in O2 was 1: 1. Sodium carbonate, nickel nitrate and manganese nitrate were weighed and added into 200 mL of deionized water, and stirred to fully dissolve the solute to obtain a mixed solution; 2 g of citric acid was added to the mixed solution, and heated and stirred at 100 ° C to evaporate to dryness to obtain a gel material; the obtained gel material was dried at 100 ° C in a vacuum drying oven, crushed, pre-calcined at 500 ° C for 5 h in a tubular furnace with a high-purity inert gas (99.9% argon) atmosphere, and then sintered at 1000 ° C for 15 h, and cooled to room temperature to obtain a pure phase layered oxide positive electrode material NaNi 0.5 Mn 0.5 O2.

[0195] The pure phase layered oxide cathode material prepared above was added to 70 mL of ethanol solvent, placed on a magnetic stirrer and stirred for 2 hours to obtain a cathode material suspension; ferrous nitrate was weighed and added to the suspension according to the mass ratio of sodium ferrous fluorophosphate to the cathode material (0.001:1); a mixed solution of sodium fluoride, sodium carbonate and ammonium dihydrogen phosphate was prepared using deionized water as a solvent, and was added dropwise to the suspension and continued to be stirred evenly; the solvent was evaporated in an oven at 100°C, and then the dried mixture was placed in a tubular furnace with an atmosphere of high-purity inert gas (99.9% argon), sintered at 600°C for 8 hours, and cooled to room temperature to obtain sodium ferrous fluorophosphate-coated NaNi 0.5 Mn 0.5 O2 positive electrode active material.

[0196] The NaNi coated with sodium ferrous fluorophosphate of Example 1-1 0.5 Mn 0.5 The O2 positive electrode active material, the conductive agent carbon black, the binder polyvinylidene fluoride (PVDF), and N-methylpyrrolidone (NMP) are stirred and mixed evenly in a weight ratio of 84.37:30:28.86:2.9:1.1 to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode collector, and the positive electrode sheet is obtained after drying, cold pressing, and slitting.

[0197] Example 1-2 to Example 1-7

[0198] The difference between this embodiment and embodiment 1-1 is that the mass fraction of sodium fluorophosphate in the positive electrode active material is different.

[0199] Example 1-8 to Example 1-9

[0200] This embodiment is different from Embodiment 1-1 in that the average particle size Dv150 of the positive electrode active material and the average thickness d of the coating layer in the cross section of the positive electrode active material are different.

[0201] Example 2-1

[0202] The difference between this embodiment and embodiment 1-1 is that the type of coating layer is different. In embodiment 2-1, the pure phase layered oxide positive electrode material prepared above is added to 70mL of ethanol solvent, placed on a magnetic stirrer and stirred for 2 hours to obtain a positive electrode material suspension; nickel nitrate is weighed and added to the suspension according to the mass ratio of sodium nickel fluorophosphate to positive electrode material (0.15:1); a mixed solution of sodium fluoride, sodium carbonate, and ammonium dihydrogen phosphate is prepared with deionized water as a solvent, and is added dropwise to the suspension and continued to be stirred evenly; the solvent is evaporated in a 95°C oven, and then the dried mixture is placed in a high-purity inert gas (99.9% argon) atmosphere tubular furnace, sintered at 500°C for 10 hours, and cooled to room temperature to obtain a positive electrode active material coated with sodium nickel fluorophosphate.

[0203] Example 3-1

[0204] According to the chemical formula of layered oxide positive electrode material Na 0.8 Ni 0.365 Fe 0.07 Mn 0.545 La 0.02 The molar ratio of different elements in O2 is 1:1. Sodium carbonate, nickel nitrate, iron nitrate, manganese nitrate and lanthanum nitrate are weighed and added into 200 mL of deionized water, and stirred to fully dissolve the solute to obtain a mixed solution; 2 g of ascorbic acid is added to the mixed solution, and heated and stirred at 85° C. to evaporate to dryness to obtain a gel material; the obtained gel material is dried at 85° C. in a vacuum drying oven, crushed, pre-calcined at 400° C. for 6 h in a tubular furnace in an atmosphere of high-purity inert gas (99.9% argon), and then sintered at 900° C. for 14 h, and cooled to room temperature to obtain a pure phase layered oxide positive electrode material Na 0.8 Ni 0.365 Fe 0.07 Mn 0.545 La 0.02 O2.

[0205] The pure phase layered oxide cathode material prepared above was added to 70 mL of ethanol solvent, placed on a magnetic stirrer and stirred for 3 hours to obtain a cathode material suspension; ferrous nitrate was weighed and added to the suspension according to the mass ratio of sodium ferrous fluorophosphate to cathode material (0.05:1); a mixed solution of sodium fluoride, sodium carbonate and ammonium dihydrogen phosphate was prepared using deionized water as a solvent, and was added dropwise to the suspension and continued to be stirred evenly; the solvent was evaporated in an oven at 85°C, and the dried mixture was then placed in a tubular furnace with an atmosphere of high-purity inert gas (99.9% argon), sintered at 800°C for 6 hours, and cooled to room temperature to obtain sodium ferrous fluorophosphate-coated Na 0.8 Ni 0.365 Fe 0.07 Mn 0.545 La 0.02 O2 positive electrode active material.

[0206] Example 3-2

[0207] The difference between this embodiment and embodiment 3-1 is that: according to the chemical formula of the layered oxide positive electrode material NaMn 0.33 Ni 0.27 Fe 0.33 Zn 0.06The molar ratio of different elements in O2 was 1:1. Sodium carbonate, manganese nitrate, nickel nitrate, ferrous nitrate and zinc nitrate were weighed and added into 200 mL of deionized water, and stirred to fully dissolve the solute to obtain a mixed solution; 1 g of citric acid was added to the mixed solution, and heated and stirred at 95°C to evaporate to dryness to obtain a gel material; the obtained gel material was dried at 95°C in a vacuum drying oven, crushed, pre-calcined at 500°C for 6 h in a tubular furnace in an atmosphere of high-purity inert gas (99.9% argon), and then sintered at 950°C for 17 h, and cooled to room temperature to obtain a pure phase layered oxide positive electrode material NaMn 0.33 Ni 0.27 Fe 0.33 Zn 0.06 O2. Then the positive electrode active material is obtained by coating.

[0208] Example 3-3

[0209] According to the chemical formula of layered oxide positive electrode material NaMn 0.33 Ni 0.27 Fe 0.33 Zn 0.06 The molar ratio of different elements in O2 was 1:1. Sodium carbonate, manganese nitrate, nickel nitrate, ferrous nitrate and zinc nitrate were weighed and added into 200 mL of deionized water, and stirred to fully dissolve the solute to obtain a mixed solution; 1 g of citric acid was added to the mixed solution, and heated and stirred at 95°C to evaporate to dryness to obtain a gel material; the obtained gel material was dried at 95°C in a vacuum drying oven, crushed, pre-calcined at 500°C for 6 h in a tubular furnace in an atmosphere of high-purity inert gas (99.9% argon), and then sintered at 950°C for 17 h, and cooled to room temperature to obtain a pure phase layered oxide positive electrode material NaMn 0.33 Ni 0.27 Fe 0.33 Zn 0.06 O2.

[0210] The pure phase layered oxide positive electrode material prepared above was added to 70 mL of ethanol solvent, placed on a magnetic stirrer and stirred for 2 hours to obtain a positive electrode material suspension; nickel nitrate was weighed and added to the suspension according to the mass ratio of sodium nickel fluorophosphate to the positive electrode material (0.15:1); a mixed solution of sodium fluoride, sodium carbonate and ammonium dihydrogen phosphate was prepared using deionized water as a solvent, and was added dropwise to the suspension and continued to be stirred evenly; the solvent was evaporated in an oven at 95°C, and then the dried mixture was placed in a tubular furnace with an atmosphere of high-purity inert gas (99.9% argon), sintered at 500°C for 10 hours, and cooled to room temperature to obtain sodium nickel fluorophosphate-coated NaMn 0.33 Ni 0.27 Fe 0.33 Zn 0.06 O2 positive electrode active material.

[0211] Embodiment 3-4

[0212] The difference between this embodiment and embodiment 3-3 is that the layered oxide in the positive electrode active material is Na 0.8 Ni 0.36 5Fe 0.07 Mn 0.545 La 0.02 O2. Then the positive electrode active material is obtained by coating.

[0213] Comparative Example 1

[0214] According to the chemical formula of layered oxide positive electrode material NaNi 0.5 Mn 0.5 The molar ratio of different elements in O2 was 1: 1. Sodium carbonate, nickel nitrate and manganese nitrate were weighed and added into 200 mL of deionized water, and stirred to fully dissolve the solute to obtain a mixed solution; 2 g of citric acid was added to the mixed solution, and heated and stirred at 100 ° C to evaporate to dryness to obtain a gel material; the obtained gel material was dried at 100 ° C in a vacuum drying oven, crushed, pre-calcined at 500 ° C for 5 h in a tubular furnace with a high-purity inert gas (99.9% argon) atmosphere, and then sintered at 1000 ° C for 15 h, and cooled to room temperature to obtain a pure phase layered oxide positive electrode active material NaNi 0.5 Mn 0.5 O2. Its volume is the same as that of the positive electrode active material of Example 1-1.

[0215] Comparative Example 2

[0216] According to the chemical formula of layered oxide positive electrode material Na 0.8 Ni 0.365 Fe 0.07 Mn 0.545 La 0.02 The molar ratio of different elements in O2 is 1:1. Sodium carbonate, nickel nitrate, iron nitrate, manganese nitrate, and lanthanum nitrate are weighed and added into 200 mL of deionized water, and stirred to fully dissolve the solute to obtain a mixed solution; 2 g of ascorbic acid is added to the mixed solution, and heated and stirred at 85° C. to evaporate to dryness to obtain a gel material; the obtained gel material is dried at 85° C. in a vacuum drying oven, crushed, pre-calcined at 400° C. for 6 h in a tubular furnace in an atmosphere of high-purity inert gas (99.9% argon), and then sintered at 900° C. for 14 h, and cooled to room temperature to obtain a pure phase layered oxide positive electrode active material Na 0.8 Ni 0.365 Fe 0.07 Mn 0.545 La 0.02 O2. Its volume is the same as that of the positive electrode active material of Example 1-1.

[0217] Comparative Example 3

[0218] According to the chemical formula of layered oxide positive electrode material NaMn 0.33 Ni0.27 Fe 0.33 Zn 0.06 The molar ratio of different elements in O2 was 1: 1. Sodium carbonate, manganese nitrate, nickel nitrate, ferrous nitrate and zinc nitrate were weighed and added into 200 mL of deionized water, and stirred to fully dissolve the solute to obtain a mixed solution; 1 g of citric acid was added to the mixed solution, and heated and stirred at 95°C to evaporate to dryness to obtain a gel material; the obtained gel material was dried at 95°C in a vacuum drying oven, crushed, pre-calcined at 500°C for 6 h in a tubular furnace in an atmosphere of high-purity inert gas (99.9% argon), and then sintered at 950°C for 17 h, and cooled to room temperature to obtain a pure phase layered oxide positive electrode active material NaMn 0.33 Ni 0.27 Fe 0.33 Zn 0.06 O2. Its volume is the same as that of the positive electrode active material of Example 1-1.

[0219] Test Section

[0220] 1) First coulombic efficiency test: Combine the above-mentioned positive electrode plate and sodium plate into a button cell. At 2.5-4.35V, charge the button cell at 1C to 4.35V, then charge at a constant voltage at 4.35V to a current of 0.05C, let it stand for 5 minutes, and then discharge it at 1C to 2.5V. The ratio of the discharge capacity to the charging capacity at this time is the first coulombic efficiency at a rate of 1C.

[0221] 2) Capacity retention rate test: Combine the above positive electrode plate and sodium plate into a button battery, charge the button battery to 4.35V at 1C at 2.5-4.35V and 25℃, then charge it to 0.05C at a constant voltage at 4.35V, let it stand for 5 minutes, then discharge it to 2.5V at 1C, and measure the discharge capacity of this step. Repeat this process for 200 cycles and calculate the capacity retention rate.

[0222] According to the results in Table 1, compared with Comparative Example 1, Example 3-1 compared with Comparative Example 2, and Example 3-2 compared with Comparative Example 3, with equal mass of positive electrode active material in the positive electrode sheet, the positive electrode material of the embodiments has improved structural stability of the positive electrode active material on the basis of higher coulombic efficiency, thereby improving the cycle stability of the battery cell containing the positive electrode active material.

[0223] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.

[0224]

Claims

1. A positive electrode active material for a sodium ion battery, wherein: include: Sodium-containing metal oxide particles; as well as A coating layer at least partially covers the sodium-containing metal oxide particles, The coating layer includes sodium fluorophosphate, and the sodium fluorophosphate includes one or more of Fe and Ni elements.

2. The positive electrode active material according to claim 1, wherein Based on the total mass of the positive electrode active material, the positive electrode active material includes sodium fluorophosphate in an amount W1 of 0.8% to 5%, optionally 2% to 4%.

3. The positive electrode active material according to claim 1 or 2, wherein The average particle size Dv of the positive electrode active material 1 50 and the average thickness d of the coating layer in the cross section of the positive electrode active material is 1: (0.02-0.2), can be selected as 1:(0.024-0.18).

4. The positive electrode active material according to any one of claims 1 to 3, wherein The average particle size Dv of the positive electrode active material 1 50 is 5μm-20μm, and can be optionally 5μm-15μm.

5. The positive electrode active material according to any one of claims 1 to 4, wherein The average thickness d of the coating layer is 0.1-2 μm, optionally 0.2-1.5 μm, and more optionally 0.5-1 μm.

6. The positive electrode active material according to any one of claims 1 to 5, wherein The structural formula of the sodium fluorophosphate salt is Na x A y (PO4) z F, wherein A includes any one or a combination of Fe and Ni elements; 0< x≤2, 0<y≤2, 0<z≤2.

7. The positive electrode active material according to any one of claims 1 to 6, wherein x+y-3Z=1 or x+2y-3Z=1.

8. The positive electrode active material according to any one of claims 1 to 6, wherein the sodium-containing metal oxide particles include a structural formula of Na a Ni b Co c Mn f M d O e of metal oxides, wherein 0.5≤a≤1.2, 0≤b≤2, 0≤c≤2, 0≤f≤1, 0≤d≤1.5, 1≤e≤4, A includes one or more of Li and Na; M includes any one of Fe, Al, Zr, Y, La, Zn, Ca, Li, Rb, Cs, W, Ce, Mo, Ba, Ti, Mg, Ta, Nb, V, Sc, Sr, B and Cu elements, or a combination of at least two of them; optionally, b+c+d+f=1 or b+c+d+f=2.

9. A method for preparing a positive electrode active material according to any one of claims 1 to 8, comprising: mixing an aqueous solution containing a sodium fluorophosphate precursor with an organic suspension containing a sodium-containing metal oxide to obtain a mixed solution; The solvent in the mixed solution is removed, and solid-phase sintering is performed in a protective atmosphere to convert the sodium fluorophosphate salt precursor into sodium fluorophosphate salt and form a coating layer that at least partially covers the layered metal oxide particles to obtain a positive electrode active material.

10. The method according to claim 9, wherein: The sodium fluorophosphate precursor includes a soluble fluorine-containing salt, a soluble metal salt, and a soluble phosphate, wherein the soluble metal salt includes a salt of any one or at least two metal elements of Fe and Ni and a soluble sodium salt; Optionally, the soluble sodium salt and the soluble phosphate are the same substance; Optionally, the soluble sodium salt and the fluoride-containing salt are the same substance.

11. The method according to claim 10, wherein: The method satisfies at least one of the following conditions: The organic suspension includes an organic solvent, and the organic solvent includes at least one of ethanol and acetone; The solid phase sintering temperature is 500-950 degrees Celsius, and can be optionally 600-800 degrees Celsius.

12. A positive electrode sheet, comprising a positive electrode current collector and a positive electrode film layer located on at least one side of the positive electrode current collector, wherein the positive electrode film layer comprises the positive electrode active material according to any one of claims 1 to 8, or the positive electrode active material prepared by the method according to any one of claims 9 to 11.

13. A battery cell, wherein: Comprising the positive electrode sheet according to claim 12.

14. A battery, wherein: The invention comprises a plurality of battery cells according to claim 13 .

15. An electrical device, wherein: A battery according to claim 14, for providing electrical energy.

Citation Information

Patent Citations

  • NaCrO2 (at) transition metal sodium fluorophosphate / C composite material and preparation and application thereof in sodium ion battery

    CN114597389A

  • Multi-layer coated sodium ion battery positive electrode material, preparation method and sodium ion battery

    CN115132987A

  • Sodium-ion battery positive electrode material, preparation method thereof, sodium-ion battery positive electrode plate and sodium-ion battery

    CN115763717A

  • Sodium-ion battery positive electrode material as well as preparation method and application thereof

    CN115763768A

  • Complex metal oxide, positive electrode active material for sodium secondary battery, positive electrode for sodium secondary battery, and sodium secondary battery

    JP2013203565A